Draft Annual Plan 2010-11 Orissa Volume-II Government of Orissa - Planning Commission (Planning Commission, 2010)
Agriculture and Allied Activities, Rural Development, Special Area Programmes, Irrigation and Flood Control, Energy, Industry and Minerals, Transport, Science, Technology and Environment, General Economic Services, Social Services, General Services.
Government of Orissa, Planning and Co-ordination Department
Government of Orissa